Odpowiedź :
1.
[tex]m \neq 0[/tex]
2.
[tex]\Delta>0[/tex]
[tex]\Delta=(m+1)^2-4\cdot m\cdot2=m^2+2m+1-8m=m^2-6m+1[/tex]
[tex]\Delta_m=(-6)^2-4\cdot1\cdot1=36-4=32[/tex]
[tex]\sqrt{\Delta_m}=\sqrt{32}=4\sqrt2[/tex]
[tex]m_1=\frac{6-4\sqrt2}{2}=3-2\sqrt2[/tex]
[tex]m_2=\frac{6+4\sqrt2}{2}=3+2\sqrt2[/tex]
[tex]m\in(-\infty;3-2\sqrt2)\cup(3+2\sqrt2;+\infty)[/tex]
3.
[tex]x_1^2+x_2^2=5[/tex]
[tex]x_{1}^{2}+x_{2}^{2}=(x_{1}+x_{2})^{2}-2x_{1}x_{2}=\frac{b^2-2ac}{a^2}[/tex]
[tex]\frac{(m+1)^2-2\cdot m\cdot2}{m^2}=5[/tex]
[tex]\frac{m^2+2m+1-4m}{m^2}=5[/tex]
[tex]\frac{m^2-2m+1}{m^2}=5[/tex]
[tex]m^2-2m+1=5m^2[/tex]
[tex]m^2-2m+1-5m^2=0[/tex]
[tex]-4m^2-2m+1=0\ \ \ |:(-1)[/tex]
[tex]4m^2+2m-1=0[/tex]
[tex]\Delta=2^2-4\cdot4\cdot(-1)=4+16=20[/tex]
[tex]\sqrt{\Delta}=\sqrt{20}=2\sqrt5[/tex]
[tex]m_1=\frac{2-2\sqrt5}{-8}=\frac{-1+\sqrt5}{4}[/tex]
[tex]m_2=\frac{2+2\sqrt5}{-8}=\frac{-1-\sqrt5}{4}[/tex]
Z 1,2 i 3
[tex]m=\frac{-1-\sqrt5}{4}[/tex]